Digitalization and Designing a Medicinal Plants Web-based Information System for Supporting Herbal Tourism in Kima Bajo Village North Minahasa Regency - Rahman, Asep; Kalua, Aditya Lapu; Rompis, Lianly (Universitas Teknokrat Indonesia, 2024)
Kima Bajo Village is one of the villages in North Minahasa Regency which has great herbal tourism potential. In particular, Kima Bajo Village is known for having a wealth of knowledge about traditional medicine, especially coastal medicinal plants. Apart from that, Kima Bajo Village is a buffer area for the Likupang tourist destination, which is one of the super priority destinations (DSP). Along with technological advances, digitalization has become a solution for optimizing tourism potential. Digitalization of medicinal plants can increase the attractiveness of herbal tourism in Kima Bajo Village and its surroundings. Digitalization in the form of creating a digital database, has an important role in developing herbal tourism in Kima Bajo Village, North Minahasa Regency. In this case, digitalization has a very important role in making it easier to access information and understanding about medicinal plants, both for local people and tourists. Our activity involved mapping the location and spatial distribution of these medicinal plants. The mapping was carried out based on the position of the coordinate point where the medicinal plant population was found in the Kimabajo area. The output of this activity was increasing public services regarding herbal tourism information in digital and web-based form. Apart from that, scientific publications, mass media publications and activity video publications were the output of the activity so that it can contribute optimally to partners and universities.